ALTERNATIF PENYELESAIAN SENGKETA MENURUT ADAT HAKOHIK (PERANG TANDING) SUKU TETUN DI KABUPATEN BELU - don Rade, Stefanus; Louisa Henukh Ledoh, Putri Marry; Fernanda Maia, Ledythria; Bendito Mitang, Yohanes; O. Waang, Andre Wiliam; Tuku Tiwa, Aprilianus; Gae Soro, , Elroswit E. Teresa; Snak, Stefanus (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Disputes or problems that arise in human life often require resolution to maintain peace and social harmony. One of the ways of resolving disputes that is still applied in the people of Belu Regency is through Hakohik customary law, which is a tradition of fighting or struggle between two opposing parties. This customary law is used to resolve disputes, both criminal ones, such as insults or slander, as well as non-criminal disputes, such as land disputes or infidelity. In dispute resolution using Hakohik, both parties involved traditional elders to decide the case customarily, by involving certain rituals and procedures that have a deterrent effect. This process aims to restore the honor and dignity of those who feel aggrieved, as well as to maintain solidarity and peace in indigenous communities. Although this method has existed for hundreds of years, Hakohik is still accepted and used as a dispute resolution system that is considered effective by the Tetun people in Belu Regency. Through this research, it is hoped that it can provide a deeper understanding of the role and mechanism of Hakohik customary law in the indigenous people of Belu Regency, as well as its relevance in dispute resolution in the modern era